Reproductive Ecology of Northern Bobwhite in North Florida - Theodore DeVos; Brad S. Mueller (National Quail Symposium Proceedings, 2017)
Brood habitat use and summer mortality of northern bobwhite (Colinus virginianus) chicks and adults were studied from 1984 to 1986 at Tall Timbers Research Station near Tallahassee, Florida. Adult bobwhite (n = 134) were radio-tagged and monitored throughout the breeding season. Fifty-four nests were located and 227 bobwhite chicks were monitored to determine reproductive output and brood status. Counting chicks on the roost at night provided reliable estimates of brood size reduction. Chick loss rates were 62% to 2 weeks and 71 % to 1 month posthatch. Adult mortality from 15 May to 15 October for combined years was 31 %. Seventy-one percent of females surviving to 15 October produced a brood (defined as> 1 chick surviving to 2 weeks of age). Fourteen percent of males which survived the summer incubated a nest and produced a brood. Brood locations were analyzed for vegetative structure, composition, and insect abundance and compared to random plots. An inverse correlation (P < 0.05) existed between insect abundance and brood home ranges at 2 weeks. However, there was no correlation between insect density and chick mortality (P > 0.05). Brood locations had a greater (P < 0.05) occurrence of Compositae, Gramineae, Leguminosae, Rosaceae, and shrubs than random locations. Preferred brood areas were old (>5 years), fallow fields with a scattering of shrubby thickets and a relatively open tree canopy. Two cases of double clutching occurred in which females successfully raised a brood to 1 month of age and subsequently were found incubating a second nest.
Keywords: brood; Colinus virginianus; habitat; mortality; northern bobwhite; north Florida